(untitled) (Zaporizhzhia Historical Review, 2021)
The article deals with the idiomatic expressions taking into account the mentality content and contrastivetypological method, in particular, for investigation of the linguistic picture of the world that is the verbal interpretation by the linguistic societies of the surrounding world and people themselves in that world.